2021
DOI: 10.1097/mjt.0000000000001413
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke After Transcatheter Aortic Valve Implantation: Epidemiology, Mechanism, and Management

Abstract: Background: Transcatheter aortic valve implantation (TAVI) has become an established and increasingly used approach for management of severe symptomatic aortic stenosis, showing similar or even superior outcomes compared with standard surgical aortic valve replacement (SAVR). Stroke after TAVI is a relatively rare, but serious complication, associated with potential prolonged disability and increased mortality. Areas of Uncertainty: The overall incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Our study has demonstrated that Lotus and Sapien 3 had the highest and lowest stroke risk among the newer devices, respectively. Previous studies suggested that most of the TAVI related strokes were embolic and developed mainly intraprocedural 106 . One possible explanation for an increased stroke risk with the Lotus valve could be that repositioning of the retrievable valve may increase the frequency of friction between the valve prosthesis and landing zone, which, in turn, may increase the risk of plaque abrasion, causing embolization and subsequent cerebrovascular events 96 , 97 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study has demonstrated that Lotus and Sapien 3 had the highest and lowest stroke risk among the newer devices, respectively. Previous studies suggested that most of the TAVI related strokes were embolic and developed mainly intraprocedural 106 . One possible explanation for an increased stroke risk with the Lotus valve could be that repositioning of the retrievable valve may increase the frequency of friction between the valve prosthesis and landing zone, which, in turn, may increase the risk of plaque abrasion, causing embolization and subsequent cerebrovascular events 96 , 97 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, during TAVR, it is hypothesized that the manipulation of large devices into the aortic arch and through the calcified native valve might mobilize and fragment atherosclerotic plaques that are prone to embolization in the cerebral circulation [ 44 ]. Structural and procedural concerns are considered the major periprocedural risk conditions [ 45 ]: aortic valve area or aortic annulus size, the degree of aortic leaflet calcification, pure aortic stenosis, high gradients, the degree of aortic atherosclerotic burden (such as porcelain aorta), as well as procedure time, repositioning of the bioprosthesis, post-dilation, the degree of anticoagulation, and the experience of the interventionalist. Ischemic stroke occurring >1 year from TAVR is named late stroke, and although its etiology is less understood, it seems to be mainly associated with patient characteristics: new-onset AF, HF, diabetes mellitus, systemic inflammatory diseases, thrombophilia, and chronic kidney disease.…”
Section: Cerebral Protection In Cath Labsmentioning
confidence: 99%
“…Despite the minimal invasive nature of the procedure, complications such as procedural stroke may occur in some patients due to embolisation of debris from the valve or the vasculature. The overall incidence of 30‐day stroke in TAVI patients is 3%–4% 2 . Risk predictors for acute stroke after TAVI are generally related to procedural factors, whereas late stroke is mainly associated with patient characteristics, with a variable impact on cognitive function 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of 30‐day stroke in TAVI patients is 3%–4% 2 . Risk predictors for acute stroke after TAVI are generally related to procedural factors, whereas late stroke is mainly associated with patient characteristics, with a variable impact on cognitive function 2 . Periprocedural ischemic lesions are frequent but mostly clinically silent.…”
Section: Introductionmentioning
confidence: 99%